Controlling odors from sewage sludge using ultrasound coupled with Fenton oxidation. (1st October 2016) - Liu, Nuo; Gong, Changxiu; Jiang, Jianguo; Yan, Feng; Tian, Sicong
Abstract: We examined the effects of ultrasound (U), Fenton oxidation (F), and ultrasound coupled with Fenton oxidation (U + F) pre-treatments (prior to anaerobic digestion) on the elimination of odorous compounds. The results demonstrated that U promoted odor release, while the coupled treatment and F alone decreased odor release. After 20-min treatments, the concentration of dissolved sulfide (S 2− ) under the coupled U + F treatment declined from 17.4 mg/L to 8.1 mg/L, decreasing by more than 50% and 34%, respectively, for U alone and F alone. In addition, the dissolved sulfate (SO4 2− ) concentration under couple U + F treatment significantly increased in sewage sludge from 200 mg/L to 390.6 mg/L, up 95.3% compared to U alone and 5% compared to F alone. This illustrates the oxidation process from S 2− to SO4 2− . Throughout experimentation, SO4 2− was odorless and stable, highlighting the mechanism of odor control. Thus, combining U and F into a single coupled treatment proved to be a better alternative pretreatment for controlling sludge odor compared to the U and F alone and can effectively decrease potential odor release. Highlights: Ultrasound coupled Fenton treatment was submitted for sludge odor elimination. The U + F treatment significantly reduce the odor release potential of sludge. Clarify the mechanism of sludge odor elimination after U + F treatment. U + F treatment proved to be a better odor control effect than U and F alone.